Performance Evaluation of Indian Mutual Funds During Bull and Bear Periods - Mishra, Rajesh; Ahuja, Vishal (Indian Journal of Finance, 2016)
The present paper evaluated the performance of 47 Indian mutual funds for two separate periods of January 8, 2008 to March 9, 2009 and March 9, 2009 to June 30, 2014 characterized by down period (negative market return of 59% ) and up period (positive market return of 67%), respectively. The funds were evaluated on the basis of risk adjusted performance measures like Sharpe measure, Treynor measure, information ratio, Sortino ratio, M Square ; whereas, Jensen measure, Fama net selectivity , Treynor-Mazuy (1966), and Henriksson-Merton (1981) models were used to examine the selectivity and timing skills of fund managers. Results for various risk adjusted performance measures revealed that funds performed poorly during the down period and during the overall period of the study, and also in a different way during down and up periods. The study also found that majority of the funds were able to show signs of selectivity skills during up and overall periods ; whereas, strong evidence of lack of market timing skills was found for all the periods.